The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1590/s1516-35982000000300035
|View full text |Cite
|
Sign up to set email alerts
|

Fracionamento dos carboidratos e cinética de degradação in vitro da fibra em detergente neutro da extrusa de bovinos a pasto

Abstract: RESUMO -Os objetivos do presente trabalho foram a caracterização e a determinação das estimativas dos parâmetros relativos à cinética de degradação ruminal dos carboidratos, em amostras de extrusa de animais mantidos em pastagem natural da Zona da Mata (MG), nas estações chuvosa e seca do ano. Para obtenção de amostras representativas, foram usados quatro animais fistulados no esôfago durante dois períodos experimentais na estação chuvosa, e três destes animais por dois períodos experimentais na estação seca, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
3
8

Year Published

2000
2000
2016
2016

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 14 publications
4
7
3
8
Order By: Relevance
“…Nonetheless, the CNCPS system assumes that fraction B 2 is homogeneous and shows a single specific growth rate. Working with natural pastures, Vieira et al (2000b) found average values of 0.0357 h -1 , which was a result close to the estimates obtained in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Nonetheless, the CNCPS system assumes that fraction B 2 is homogeneous and shows a single specific growth rate. Working with natural pastures, Vieira et al (2000b) found average values of 0.0357 h -1 , which was a result close to the estimates obtained in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Besides, other important quantitative variables in the feeds can be estimated, such as the energy availability and daily amount of metabolizable protein, which enables the prediction of animal performance based on known dietary inputs (Vieira et al, 2000c;Jardim et al, 2013;Jardim et al, 2015;Higgs et al, 2015). In the present study (Table 4), the average RF(I) was approximately 32% greater than RF(D), a situation that was also observed by Vieira et al (2000b) based on extrusa samples taken from a tropical grassland.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations